ANALISIS PENGARUH INFLASI, BI RATE, KURS RUPIAH/US$, DAN HARGA EMAS DUNIA TERHADAP INDEKS HARGA SAHAM SEKTOR KEUANGAN PADA BURSA EFEK INDONESIA PERIODE 2010-2014 - Puspitarani, Shinta; Sampurno, R. Djoko (Diponegoro Journal of Management, 2016)
This study aims to analyze the effect of inflation rate, BI Rate, Rp/US$ exchange rate, and world gold price to finance sector stock price index in Indonesia Stock Exchange during January 2010 until December 2014. The sample used in this study are secondary data consist of monthly closing price of finance sector stock price index. This study used multiple linear regression analysis using SPSS 20 application. Hypothesis test used using t-test to test the effect of independent variable to dependent variable individually. F-test will be used to test the effect of dependent variable simultaneously in 5% significant level. The results of this study indicate that only exchange rate that have negative and significant effect to finance sector stock price index. While, inflation rate, BI Rate, and world gold price has no significant effect to finance sector stock price index.